2021
DOI: 10.3390/ijerph18042155
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Thoracic Pain Using Machine Learning: A Case Study from Baja California, Mexico

Abstract: Thoracic pain is a shared symptom among gastrointestinal diseases, muscle pain, emotional disorders, and the most deadly: Cardiovascular diseases. Due to the limited space in the emergency department, it is important to identify when thoracic pain is of cardiac origin, since being a symptom of CVD (Cardiovascular Disease), the attention to the patient must be immediate to prevent irreversible injuries or even death. Artificial intelligence contributes to the early detection of pathologies, such as chest pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For more accurate results, it was suggested to compare patients’ responses with responses collected by healthy individuals [ 26 ]. In a case series study, Rojas-Mendizabal et al performed an analysis of 27 variables, which included demographic and clinical parameters, in order to evaluate the origin of thoracic pain and determine a possible correlation between these parameters and the presence of cardiac pain, managing to obtain a mean accuracy of 96% [ 29 ]. Rogachov et al acquired resting-state functional MRI and quantified frequency-specific regional low-frequency oscillations (LFOs) in patients with chronic pain and ankylosing spondylitis and, using an ML approach, found that higher frequencies can be used to make generalizable inferences about patients’ average pain ratings (trait-like pain) but not current (i.e., state-like) pain levels [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For more accurate results, it was suggested to compare patients’ responses with responses collected by healthy individuals [ 26 ]. In a case series study, Rojas-Mendizabal et al performed an analysis of 27 variables, which included demographic and clinical parameters, in order to evaluate the origin of thoracic pain and determine a possible correlation between these parameters and the presence of cardiac pain, managing to obtain a mean accuracy of 96% [ 29 ]. Rogachov et al acquired resting-state functional MRI and quantified frequency-specific regional low-frequency oscillations (LFOs) in patients with chronic pain and ankylosing spondylitis and, using an ML approach, found that higher frequencies can be used to make generalizable inferences about patients’ average pain ratings (trait-like pain) but not current (i.e., state-like) pain levels [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decision trees (DT) [14,22,29,34] Gradually reject classes assigned into multistage decision systems to accept a final class. In pain medicine, decision trees algorithms such as classification and regression trees have been used…”
Section: Machine Learning Algorithm Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations